Abnormal colposcopic images in patients with preinvasive cervical lesions - Adnan Babović (Journal of Health Sciences, 2013)
Introduction: The objective of the study was to determine frequency and to compare frequency of the abnormal colposcopic images in patients with low and high grade pre-invasive lesions of cervix. Methods: Study includes 259 patients, whom colposcopic and cytological examination of cervix was done. The experimental group of patients consisted of patents with pre-invasive low grade squamous intraepithelial lesion (LSIL) and high grade squamous intraepithelial lesion (HSIL), and the control group consisted of patients without cervical intraepithelial neoplasia (CIN). Results: In comparison to the total number of satisfactory fi ndings (N=259), pathological findings were registered in N=113 (43.6 %) and abnormal colposcopic fi ndings in N=128 (49.4%). The study did not include patients with unsatisfactory fi nding N=22 (8.5%). Abnormal colposcopic image is present most frequently in older patients but there are no statistically important difference between age categories (Pearson Chi-Square 0.47, df -3, p=0.923). Frequency of abnormal colposcopic fi ndings (N=128) is the biggest in pathological cytological (N=113) and HSIL 58 (45.3%), LSIL 36 (28.1%). There is statistically signifi cant difference in frequency of abnormal colposcopic images in patients with low-grade in comparison to patients with high-grade pre-invasive cervix lesions (Chi-Square test, Pearson Chi-Square 117.14, df-12 p<0.0001). Conclusion: Thanks to characteristic colposcopic images, abnormal epithelium is successfully recognized, but the severity grade of intraepithelial lesion cannot be determined.